1980
DOI: 10.1042/bj1920829
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-activated thiol-proteinase activity in the fusion of rat erythrocytes induced by benzyl alcohol

Abstract: 1. Rat erythrocytes were fused by incubation with benzyl alcohol and Ca2+. 2. Cell fusion was inhibited by EGTA, N-ethylmaleimide, tetrathionate, iodoacetamide, cystamine, Tos-Lys-CH2Cl, and to a lesser extent by Tos-Phe-CH2Cl. Phenylmethanesulphonyl fluoride, Tos-Arg-OMe and histamine did not inhibit cell fusion. 3. Gel electrophoresis of membrane proteins from "ghosts" of the erythrocytes treated with benzyl alcohol showed that a high-molecular-weight polymer was present: this was consistent with the entry i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Calcium seems to be a requirement for most types of fusion; it has been suggested that the function of fusion-promoting agents is to introduce calcium into the cell (33). The actual role of protease activity in the overall fusion process has not been clarified (31,33,34). We show here that the introduction of calcium per se and the activation of protease activity do not suffice for the induction of fusion.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Calcium seems to be a requirement for most types of fusion; it has been suggested that the function of fusion-promoting agents is to introduce calcium into the cell (33). The actual role of protease activity in the overall fusion process has not been clarified (31,33,34). We show here that the introduction of calcium per se and the activation of protease activity do not suffice for the induction of fusion.…”
Section: Discussionmentioning
confidence: 69%
“…The protease(s) necessary for fusion could be activated directly or indirectly (31) (i.e., via another enzyme) by calcium. Calcium seems to be a requirement for most types of fusion; it has been suggested that the function of fusion-promoting agents is to introduce calcium into the cell (33). The actual role of protease activity in the overall fusion process has not been clarified (31,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the fusion of human erythrocytes by chlorpromazine and oleoylglycerol, the fusion of rat red blood cells by benzyl alcohol and the associated degradation of their membrane proteins is prevented by agents that chelate Ca2+ and by iVethylmaleimide [20]. This indicates that the Cat+-activated cysteine proteinase is more important in these cells, and it is interesting that the content of calpastatin, an endogenous inhibitor of the Ca'+-activated, cysteine proteinase known as calpain I is extremely small in rat erythrocytes, whiIe in human erythrocytes there is much more inhibitor than enzyme [21].…”
mentioning
confidence: 99%
“…Proteinases are important in chemically induced cell fusion , and the fusion of erythrocytes by some chemical fusogens involves the proteolysis of ankyrin by a serine proteinase [23] and the proteolysis of band 3 by a calcium-activated proteinase [23,24]. Inhibitors of these proteolytic activities inhibit fusion.…”
Section: Perturbation Of Membrane Proteinsmentioning
confidence: 99%